Significance of Healthy Family Structure in Preventing Child Sexual Abuse: A Prospective Controlled Study - Mustafa Talip Sener; Yuksel Anci; Onur Burak Dursun (Medicine Science, 2014)
The aim of this study was to determine the socio-demographic characteristics of victims, parents, and accused or suspected child abusers, and to evaluate the conditions that constitute the risk factors for children falling victim to sexual abuse in Eastern Anatolian Region of Turkey. Personal data files of 63 victims of child sexual abuse were analyzed and compared with 201 individuals in a control group. The children’s age, gender, educational level, number of siblings, and the nature of the event they experienced, were all examined. In addition, parents’ educational and economic levels; and parents’ relationship, were also evaluated. Of the victims 66.7% were female (n=42), while the average age of the victims was 14.2 years. A total of 52.4% (n=33) of the victims were exposed to major crime, and 47.6% (n=30) were exposed to simple sexual activity. Risk factors for children who were exposed to sexual abuse were parental conflict, low educational level of the father, non-working father, low economic level of the family, and crowded family. Domestic violence negatively affects family members, especially children, and is a main risk factor for children becoming victims of abuse. [Med-Science 2014; 3(1.000): 1046-53]